Analisis Faktor-Faktor yang Memengaruhi Kepatuhan Pajak pada Mahasiswa Akuntansi di Universitas di Pulau Jawa sebagai Potensial Wajib Pajak - Heriana, Kamiliya Muthia Azra; Irawan, Ferry (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2024)
This study analyses the factors affecting tax compliance among accounting students on Java Island, considering them potential taxpayers. The research utilizes a sample of 172 respondents, selected through accidental sampling, with sample size determined using the Lemeshow formula. Data were collected via an online questionnaire and analyzed using the Partial Least Squares (PLS) method with the SmartPLS application. The findings reveal that tax knowledge, tax sanctions (both administrative and criminal), tax morale, and tax digitalization positively and significantly impact tax compliance among accounting students on Java Island. Strategic actions are recommended to enhance compliance, including improving tax education programs, enforcing strict and fair penalties, conducting tax awareness campaigns, and advancing digital technology in the tax system.